Internalizing Wasatiyah Values in Islamic Education for Religious Moderation - Abdan Rahim; Zulhijra Zulhijra; M. Arsyad Almakki; Mardani Mardani (SYAMIL: Journal of Islamic Education, 2025)
This study explores the implementation of wasatiyah (Islamic moderation) principles within Islamic Religious Education (PAI) Indonesia. In response to rising religious intolerance among youth and the national imperative to promote social cohesion, this research examines how moderation is internalized through educational practices. Religious moderation is critical in multicultural societies, yet its implementation in Islamic education remains understudied. Utilizing a qualitative case study approach, data were collected via interviews, classroom observations, focus group discussions, and document analysis over one academic semester. Findings indicate that has systematically incorporated wasatiyah through interactive teaching methods, contextual discussions, and value-based modeling. Students demonstrated cognitive understanding, affective alignment, and behavioral expression of moderate Islamic values. The integration of Islamic educational philosophy, Bloom’s Taxonomy, and Bandura’s Social Learning Theory facilitated a comprehensive pedagogical framework. Key enabling factors included strong school leadership, teacher competence, and parental support, while challenges such as limited instructional time and digital radicalism persist. This research contributes a theoretical model and practical roadmap for embedding religious moderation into PAI curricula, offering replicable insights for similar educational contexts. The study affirms the transformative potential of wasatiyah-based education in fostering tolerant, reflective, and socially responsible Muslim youth.